Lessons from lung transplantation: Cause for redefining the pathophysiology of pulmonary hypertension in gaucher disease. (2019) - Goobie, Gillian C.; Sirrs, Sandra M.; Yee, John; English, John C.; Bergeron, Celine; Nador, Roland; Swiston, John R.; Mistry, Pramod K.; Paquin, Wendy; Levy, Robert D.
Abstract: Background: Gaucher disease type 1 (GD1) is a lysosomal storage disease rarely resulting in end stage pulmonary hypertension (PH) and interstitial lung disease. There have only been two previous case reports of patients with GD1 receiving lung transplants. Case presentation: We report a case of successful bilateral sequential lung transplantation in a patient with end-stage GD1-related PH. Prior to transplant, the patient was on enzyme replacement therapy with imiglucerase and pulmonary vasodilator therapy with bosentan, sildenafil and epoprostenol. The patient had pre-transplant comorbidities of prior splenectomy and osteopenia. She underwent bilateral sequential lung transplantation with basiliximab, methylprednisolone and mycophenolate mofetil induction. Her explanted lungs demonstrated severe pulmonary arterial hypertensive changes, but no Gaucher cells. She was maintained on MMF, tacrolimus, prednisone, imiglucerase and warfarin post-transplant. Her post-transplant course was complicated by hemorrhagic shock, prolonged support with extracorporeal membrane oxygenation, and acute renal failure requiring dialysis. Despite these complications, the patient was discharged and is doing well nine months post-transplantation. Conclusions: This is one of only three reported cases of lung transplantation in patients with GD1. Each case has involved previously splenectomised, female patients with GD1. This is the first to report transplantation in a patient with severe PH and no pulmonary parenchymal disease. As evidenced in our patient, long term treatment with imiglucerase may eliminate the Gaucher cells in the lungs. The PH in these patients is most consistent with pulmonary arterial hypertension, raising the question of whether this should be reclassified as WHO Group 1 PH.